THE DISTINGUISHING HUMAN LANGUAGE FROM ANIMAL COMMUNICATION SYSTEMS (American Journal of Interdisciplinary Research and Development, 2024)
This article explores the distinctive features of human language that set it apart from animal communication systems. It examines the complexity, structure, and functionality of human language, highlighting aspects such as syntax, semantics, and the capacity for abstraction and creativity. In contrast, animal communication systems are analyzed in terms of their limited flexibility, lack of syntactic rules, and specific signaling functions. By comparing these systems, the article underscores the unique attributes of human language, including its infinite generativity, displacement, and cultural transmission. This analysis contributes to a deeper understanding of the cognitive and evolutionary underpinnings of language and communication.